Leading and Implementing Business Change Management : Making Change Stick in the Contemporary Organization. - Jones, David J. (Taylor and Francis, 2013)
Being change capable is the ""new normal"" for today's growth-minded organizations. The ""do more with less"" strategies of the past are no longer effective in preparing organizations to meet the increasing challenges for growth, competitiveness and innovation required of them in this new era. Using an integrated, scalable and flexible framework, the text provides tools which can be readily customized and applied to initiatives across or within stages of the business change management lifecycle. Drawing on real life case studies and examples of best practice this book will provide a conceptua